Metformin for diabetes prevention: insights gained from the Diabetes Prevention Program/Diabetes Prevention Program Outcomes Study - Aroda, Vanita R. (Diabetologia, 2017)
The largest and longest clinical trial of metformin for the prevention of diabetes is the Diabetes Prevention Program/Diabetes Prevention Program Outcomes Study (DPP/DPPOS). In this review, we summarise data from the DPP/DPPOS, focusing on metformin for diabetes prevention, as well as its long-term glycaemic and cardiometabolic effects and safety in people at high-risk of developing diabetes. The DPP (1996–2001) was a RCT of 3234 adults who, at baseline, were at high-risk of developing diabetes. Participants were assigned to masked placebo (n = 1082) or metformin (n = 1073) 850 mg twice daily, or intensive lifestyle intervention (n = 1079). The masked metformin/placebo intervention phase lasted 3.2 years, with primary outcome of diabetes incidence reported early, at 2.8 years, because of demonstrated efficacy. At the end of the DPP, all participants were offered lifestyle education and 88 % (n = 2776) of the surviving DPP cohort continued follow-up in the DPPOS. Participants originally assigned to metformin continued to receive metformin, unmasked. The DPP/DPPOS cohort has now been followed for over 15 years with prospective assessment of glycaemic, cardiometabolic, health economic, and safety outcomes. After an average follow-up of 2.8 years, metformin reduced the incidence of diabetes by 31 % compared with placebo, with a greater effect in those who were more obese, had a higher fasting glucose or a history of gestational diabetes. The DPPOS addressed the longer-term effects of metformin, showing a risk reduction of 18 % over 10 and 15 years post-randomisation. Metformin treatment for diabetes prevention was estimated to be cost-saving. At 15 years, lack of progression to diabetes was associated with a 28 % lower risk of microvascular complications across treatment arms, a reduction that was no different among treatment groups. Recent findings suggest metformin may reduce atherosclerosis development in men. Originally used for the treatment of type 2 diabetes, metformin, now proven to prevent or delay diabetes, may serve as an important tool in battling the growing diabetes epidemic. Long-term follow-up, currently underway in the DPP/DPPOS, is now evaluating metformin’s potential role, when started early in the spectrum of dysglycaemia, on later-stage comorbidities, including cardiovascular disease and cancer.